Estimation of selected parameters in stabilographic image depending on physical activity level in children and adolescents - Justyna Filipowicz-Ciepły; Joanna Golec; Eżbieta Szczygieł; Dorota Czechowska; Marta Cichoń; Joanna Balicka-Bom (Rehabilitacja Medyczna, 2020)
Introduction: Balance is an extremely important component of everyday human functioning. Assessment of body balance in children can be not only a diagnostic tool, but also information about the maturation of the balance system, diversity in terms of age and sex, as well as factors affecting balance and its development. In practice, maintaining body balance is a dynamic process, consisting in "continuous loss and regaining balance". According to scientific reports, in addition to age, psychosomatic status, the development of specific sensory-motor capabilities and strategies is also influenced by the type of sport.